THE ROLE OF LEADERSHIP, AND ASSISTANCE ON FEELINGS OF HAPPINESS THROUGH SATISFACTION - Fiqry Ramadhan, Imam; Munsiyah, Fatayatul; Ilham Maliki, Budi (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Humanist management is management that originates from a sense of happiness for each member of the group. The aim of the research is to build a humanist management model to achieve innovation in teacher performance, for example building a work environment that suits employee satisfaction so as to create a comfortable working atmosphere. This type of research is quantitative with a survey method on elementary school teachers in the city of Cilegon . This research includes the mediating variable satisfaction as a predictor between the independent variables (leadership and mentoring) on the feeling of happiness in employees. The research results include 1) there is an influence of leadership on satisfaction. 2) there is an influence of leadership on feelings of happiness 3) there is an influence of mentoring on satisfaction 4) there is an influence of mentoring on feelings of happiness 5) there is satisfaction on feelings of happiness.